The subject of humanity and historical memory in the harmony of silk factory - Fan, P.W.; Yeoh, K.K.; Fan, P.. (Central China Normal Univ, 2010)
The Harmony of Silk Factory is the debut novel of Tash Aw, who grew up in Malaysia, and is now living in London. This book won the Whitbread First Novel Award in 2005. The structure of the story set in the 1940s on Malay Peninsula is divided into 3 parts. Through multi-layered narrations, this book presents rarely seen Chinese capitalists, political communist activists and the complexity of identity in the Southeast Asian society during the British colonial rule and Japanese occupation. The present author aims to expose the real facts and truth that Malaysia' s government tries to avoid.